2021
DOI: 10.1111/1759-7714.14126
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic characteristics in low‐grade fetal adenocarcinoma of the lung

Abstract: Background Low‐grade fetal adenocarcinoma of the lung (L‐FLAC) is a rare subtype of lung adenocarcinoma with undetermined histological features and genetic abnormalities. In this study, we attempted to investigate the pathological characteristics and genomic profiles of L‐FLAC. Methods Among 9839 cases of primary lung adenocarcinoma resected at Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College between January 2011 and June 2016, three cases diagnosed with L‐FLAC were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Studies reporting the clinicopathological characteristics of lowgrade fetal lung adenocarcinoma with genetic analyses are summarized in Table 1. [6][7][8][9][10][11][12] To date, 21 low-grade fetal lung adenocarcinomas, including the two in our study, have been reported. All showed β-catenin nuclear/ cytoplasmic staining.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Studies reporting the clinicopathological characteristics of lowgrade fetal lung adenocarcinoma with genetic analyses are summarized in Table 1. [6][7][8][9][10][11][12] To date, 21 low-grade fetal lung adenocarcinomas, including the two in our study, have been reported. All showed β-catenin nuclear/ cytoplasmic staining.…”
Section: Discussionmentioning
confidence: 54%
“…17 DICER1 mutations have been observed in different types of tumors and could contribute to the development of various cancers. 12 To the best of our knowledge, nine low-grade fetal lung adenocarcinoma cases, including one of our two cases, have been reported to carry DICER1 mutations (Table 1). Among the data we reviewed, only 1 case has been reported to represent familial DICER syndrome.…”
Section: Discussionmentioning
confidence: 69%
“…The characteristic histopathological features includes branch forming tubular glands lined by non‐ciliated columnar cells with a bland cytology and prominent morule formation. LGFA has a specific molecular background which is different from conventional adenocarcinoma 1,2,8 . LGFA has an aberrant nuclear/cytoplasmic expression of β‐catenin and presents mutations in this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal adenocarcinoma of the lung is extremely rare, accounting for only 0.1%–0.5% of all lung neoplasms 1,2 . It features a morphology resembling the fetal lung during the pseudoglandular stage (8–16 weeks of gestation) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Germline inactivation of DICER1 is associated with familial DICER1 syndrome [17]. DICER1 mutation has been observed in different kinds of tumors and could contribute to the development of various cancers [12].…”
Section: Discussionmentioning
confidence: 99%